Marine Phytoplankton in Port and Ship’s Ballast Water at Tanjung Priok Harbour, North Jakarta, Indonesia - Hikmah Thoha; Arief Rachman (ASEAN Journal on Science and Technology for Development, 2018)
This research aimed to study the phytoplankton community in ships’ ballast water in comparison with the natural assemblages in the waters of Tanjung Priok Harbour in Jakarta, Indonesia. Phytoplankton samples were collected between November 2011 to October 2012 from four ports of Tanjung Priok Harbour and from discharged ballast water of randomly selected ships in the port. Skeletonema, Thalassiosira, and Chaetoceros were three predominant phytoplankton genera in all samples. Ceratium and Protoperidinium were also commonly found in high densities in most samples. An unusual phytoplankton bloom (> 109 cells m-3) was observed in the ballast water sample taken in March 2012. It was unknown whether this bloom was formed inside the tank or was already present at the source. Ballast water samples of BWD11, BWM12, and BWA12 had significantly different phytoplankton community from the natural assemblages in the harbour, which increase the risk of non-indigenous phytoplankton introduction to Tanjung Priok Harbour.